Analisis Teori Dusta Umberto Eco Dalam Kasus Kopi Sianida Jessica Wongso - Hermawan, Febry; Purnomo, Hadi (Prisani Cendekia Institute, 2023)
In the cyanide coffee case of Jessica Wongso, Umberto Eco's lying theory can be applied to analyze Jessica's testimony. Based on Eco's theory of lies, lying is a complex form of communication that involves various factors, such as motivation, situation and ability to lie. Based on the available evidence, Jessica's testimony that she did not know that the coffee she gave Mirna contained cyanide is considered unreasonable. Such testimony can be considered a lie caused by several factors, such as a motivation to cover up a mistake, a desire to protect others, or an inability to remember the actual incident. The research paradigm is critical, with a qualitative research approach, which does not present specific measurements, but presents meanings from the analysis of the relationship between signs and other signs. This is in accordance with the semiotic research method, which links one sign to another to reach conclusions. The research results show that the analysis of the lie theory put forward by Umberto Eco and its application in the Cyanide Coffee case involving Jessica Wongso, can be seen how the concepts put forward by Eco can provide valuable insight in understanding the dynamics and complexity of the case. In this case, there are narrative elements constructed by the parties involved, including Jessica Wongso, the mass media and the general public. The use of strong narratives and persuasive rhetoric can influence public perception and understanding of the case. Furthermore, the concepts of play and manipulation in Eco's theory of lies are also relevant in the context of this case. There are allegations that Jessica Wongso played a role in the tragic death of Mirna Solihin by using coffee containing cyanide. Eco argues that lies and manipulation can be used to produce certain effects in communication. In this case, the alleged manipulation and games carried out by Jessica Wongso influenced the parties concerned. Apart from that, Eco's lie theory also highlights the importance of context and interpretation in understanding the truth. In this case, there are differences in interpretation and understanding between the parties involved, including Jessica Wongso, Mirna Solihin's family, and the public. The concept of multiple interpretations and subjectivity in understanding the truth can be seen as significant elements in this case.